SANUSI PANE DALAM UPAYA MENUMBUHKAN KECINTAAN TERHADAP BUDAYA DAN BAHASA INDONESIA: IMPLEMENTASI MELALUI MKWU BAHASA INDONESIA DI PERGURUAN TINGGI - Hudaa, Syihaabul; Rahman, Ahmad Syaeful (Program Studi Tadris Bahasa Indonesia, 2023)
The history of the emergence of culture and language in Indonesia has been a long process. In fact, some of them involve several important shops in it, one of which is Sanusi Pane. Sanusi pane became one of the figures who contributed in the form of literary works in which there was a mandate to foster a love for Indonesian culture and language. However, in this modern era, Sanusi Pane is not well known by the millennial generation. The purpose of writing this article is to analyze the work of Sanusi Pane, in which there is an effort to foster a love for Indonesian culture and language. Then, the researchers attempted to implement these values ​​through the Indonesian Language MKWU in universities. The method used in this research is qualitative using a content analysis approach. The text is studied using an objective literary study. By conducting an objective study, the researcher focuses on the text that is the material of the study. Then, the findings are analyzed based on aspects that contain love for culture and language. Furthermore, the findings are presented in the Indonesian language MKWU during the material history and language development.